GENIUS LOCI PADA PERKAMPUNGAN TRADISIONAL SENARU SUKU SASAK KABUPATEN LOMBOK BARAT - Ersina, Sriany; Amalia, Annisa; Sutriani, Sutriani (Department of Architecture, Faculty of Science and Technology, Alauddin State Islamic University, 2014)
Senaru traditional village located in Senaru Village Lombok West Regency. The existence of a traditional village in response to the demands of home and village which is a form of cohabitation of Sasak as the original inhabitants of this village. Literally, the genius loci is the soul of space and time, locality and region-region where architecture grows and develops that triggers the growth of the spirit of